New Zealand Policy and Restorative Justice Philosophy - Winfree, L. Thomas Jr (Crime & delinquency, 2004)
In New Zealand, selected sworn police officers called youth aid officers participate in discussions and deliberations concerning the actions required to restore the sense of community balance upset by the actions of juvenile offenders. The author explores a representative sample of all sworn police officers serving in the New Zealand Police, including a subsample of youth aid officers, looking at the nature of support for the philosophical underpinnings of restorative justice and the likely impact of such work and values on officer attitudes toward the workplace. A 1996 management survey of all branches of the New Zealand national policing organization contained a number of specific questions that tap dimensions of both restorative justice philosophy and workplace orientations. This study represents a descriptive examination of these self-reported perspectives for all sworn officers, including breakdowns by selected personal-biographical variables. Implications for the implementation of restorative justice practices within a policing organization are discussed. [ABSTRACT FROM AUTHOR]